Evaluation of a PET Radioligand to Image O -GlcNAcase in Brain and Periphery of Rhesus Monkey and Knock-Out Mouse - Paul, Soumen; Haskali, Mohammad B.; Liow, Jeih-San; Zoghbi, Sami S.; Barth, Vanessa N.; Kolodrubetz, Marcy Comly; Bond, Michelle R.; Morse, Cheryl L.; Gladding, Robert L.; Frankland, Michael P.; Kant, Nancy; Slieker, Lawrence; et al. (Journal of Nuclear Medicine, 2019)
Accumulation of hyperphosphorylated tau, a microtubule-associated protein, plays an important role in the progression of Alzheimer disease. Animal studies suggest that one strategy for treating Alzheimer disease and related tauopathies may be inhibition of -GlcNAcase (OGA), which may subsequently decrease pathologic tau phosphorylation. Here, we report the pharmacokinetics of a novel PET radioligand, F-LSN3316612, which binds with high affinity and selectivity to OGA. PET imaging was performed on rhesus monkeys at baseline and after administration of either thiamet-G, a potent OGA inhibitor, or nonradioactive LSN3316612. The density of the enzyme was calculated as distribution volume using a 2-tissue-compartment model and serial concentrations of parent radioligand in arterial plasma. The radiation burden for future studies was based on whole-body imaging of monkeys. , a mouse brain-specific knockout of was also scanned to assess the specificity of the radioligand for its target enzyme. Uptake of radioactivity in monkey brain was high (∼5 SUV) and followed by slow washout. The highest uptake was in the amygdala, followed by striatum and hippocampus. Pretreatment with thiamet-G or nonradioactive LSN3316612 reduced brain uptake to a low and uniform concentration in all regions, corresponding to an approximately 90% decrease in distribution volume. Whole-body imaging of rhesus monkeys showed high uptake in kidney, spleen, liver, and testes. In mice, brain uptake of F-LSN3316612 was reduced by 82% compared with control mice. Peripheral organs were unaffected in mice, consistent with loss of OGA expression exclusively in the brain. The effective dose of F-LSN3316612 in humans was calculated to be 22 μSv/MBq, which is typical for F-labeled radioligands. These results show that F-LSN3316612 is an excellent radioligand for imaging and quantifying OGA in rhesus monkeys and mice. On the basis of these data, F-LSN3316612 merits evaluation in humans.